The sparrow"s fall (Mt 10:29) - Stander, Hennie (HTS teologiese studies, 2005)
According to Matthew 10:29, not one sparrow will fall to the ground “apart from the Father”. The latter phrase is elliptical, and it is not clear what type of involvement from the Father is meant. This article examines how this verse is interpreted in the various Bible translations and by modern commentaries. Thereafter patristic writings are consulted in search of a solution. It shows that the interpretation of this verse is often rooted in theological doctrine.